2008
DOI: 10.1111/j.1752-248x.2008.00015.x
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus infection in oral squamous cell carcinomas: correlation with histologic variables and survival outcome in a high risk population

Abstract: Aim: Cancer of the oral cavity is extremely prevalent in Pakistan. Human papillomavirus (HPV) has been shown to play a role in the development of oral squamous cell carcinoma (OSCC) and may even improve overall and disease-free survival. The purpose of this study was to determine prevalence and types of HPV in a high risk population and its correlation with overall and disease-free survival, chewing habits and histologic variables. Material and methods:  A total of 140 patients of OSCC, having a long-term foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 38 publications
(47 reference statements)
1
7
1
Order By: Relevance
“…It is suggested that the oral cavity is exposed more intensely to the synergistic carcinogenic effect of chewing tobacco, smoking, alcohol and HPV infection. HPV infection is a significant factor that causes TP53 alteration, and we have seen that HPV infection is common in Pakistani cancer patients 47,48 . Some studies have shown strong association between TP53 expression and smoking 49,50 , betel quid chewing 51 and alcohol drinking 49,50 , but in our study, we did not found any association between patient habits (smoking, chewing tobacco and betel‐quid consumption) and TP53 overexpression.…”
Section: Discussioncontrasting
confidence: 82%
“…It is suggested that the oral cavity is exposed more intensely to the synergistic carcinogenic effect of chewing tobacco, smoking, alcohol and HPV infection. HPV infection is a significant factor that causes TP53 alteration, and we have seen that HPV infection is common in Pakistani cancer patients 47,48 . Some studies have shown strong association between TP53 expression and smoking 49,50 , betel quid chewing 51 and alcohol drinking 49,50 , but in our study, we did not found any association between patient habits (smoking, chewing tobacco and betel‐quid consumption) and TP53 overexpression.…”
Section: Discussioncontrasting
confidence: 82%
“…This yielded a positive result for 95 patients (67.9 per cent). The HPV polymerase chain reaction findings were further specified according to the type: 85 patients were HPV 16 positive, while 2 were HPV 18 positive 11 . Six patients were positive for HPV other than the 16 and 18 subtypes.…”
Section: Resultsmentioning
confidence: 99%
“…Following our 2008 study, the patients’ HPV status and clinical characteristics were already known, and the same data were utilised in our study 11 . The results were recorded by the study investigators.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clearly, the HPV status of patients with OSCC would be an important determinant for prognosis and treatment options in the future. Recently, in a retrospective study of 140 patients with primary OSCC and a long-term follow up, Ali et al reported from Karachi, Pakistan, 68% of cases to be positive for HPV (Ali et al, 2008). Approximately 90% of these cases were infected with HPV16, (Figure 3 & 4) the predominant subtype in the US population as well.…”
Section: Hpv and Oral Cancermentioning
confidence: 99%